A articulação no frevo de rua: um levantamento com trompetistas de Olinda e Recife - Oliveira, Érico Veríssimo Carvalho de (2018)
The present work aimed to describe how the trumpet players from Olinda and Recife articulate certain excerpts from a selection of frevos de rua peculiar to the repertoire of frevo orchestras. A review was made of fundamentals that characterize musical performance, among them articulation as an element of the performer's domain that interacts with different environments and social contexts. It also sought to approximate the stylistic characteristics inherent to the articulation of the frevo de rua, seeking to approach the idea of a specific accent. This is a survey in which trumpeters were interviewed with more than ten years of experience in the area. In addition to the verbal responses, the instrumental execution of the excerpts was requested. The results were analyzed qualitatively, so that it was possible to characterize and compare the articulatory processes, revealing what was cognitive, but also the practical-instrumental aspect. In this way, it was possible to contemplate the articulatory processes of the trumpet in the frevo de rua, as well as its traditions and relations with the different social contexts in which it is inserted.